PRAKTIK CREATIVE ACCOUNTING PADA KOPERASI DI JAWA TIMUR - Dian Agustia; Ade Palupi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2016)
The cooperation is characterized that its member includes the owners as well as the users of a cooperation. The cooperation financial reporrs have to be reported as a tool of accountability of the officers to the cooperation members in the annual meeting. The most essential information required in the annual meeting is the cooperation’s profits that in Indonesia is called as Sisa Hasil Usaha (SHU). In this study, a creative accountancy practice is applied as activities that is done by a business unit to report the desired surplus by implementing accountancy techniques and policies in regard with particular condition. By using descriptive statistic analysis, a cooperation with the scale area of East Java Province during the period of 2012 to 2014 has implemented a creative accountancy practice to increase or decrease profit. The cooperation officers or managers increase its SHU when its factual profit is lower; but they decrease its SHU when its factual profit is higher. The purpose of this practice is to reduce the fluctuation of SHU so that the cooperation looks stable and has no high risk for businesses. The results of this study is relevant with Scoot (2011) arguing for the opportunistic practice of cooperation managers or officers to maximize compensation contracts, debt contract, and political costs